Bank of Kalman filters for fault detection in quadrotor MAV - Pebrianti, Dwi; Rosdiyana, Samad; Mahfuzah, Mustafa; Nor Rul Hasma, Abdullah; Bayuaji, Luhur (Asian Research Publishing Network (ARPN), 2016)
Fault Detection and Identification (FDI) is a subfield of control engineering which concerns with self-monitoring system, identifying and pinpointing the type and location of failures. This study proposes the application of Kalman Filter for fault detection in quad rotor type MAV. It begins with the development of model of quad rotor, based on rigid body dynamic. The bank of Kalman filters consists of six filters that are associated with the total number of the degree of freedom of the quad rotor. The performance of the fault detection is conducted by simulation using Simulink, Matlab. The result shows that the developed bank of Kalman filters has good performance in detecting a sensor failure during a hovering condition.